Philicity of Acetonyl and Benzoyl Radicals: A Comparative Experimental and Computational Study. Issue 38 (11th June 2019) - Verschueren, Rik H.; Schmauck, Julie; Perryman, Michael S.; Yue, Hui‐Lan; Riegger, Julian; Schweitzer‐Chaput, Bertrand; Breugst, Martin; Klussmann, Martin
Abstract: In this work, the reactivities of acetonyl and benzoyl radicals in aromatic substitution and addition reactions have been compared in an experimental and computational study. The results show that acetonyl is more electrophilic than benzoyl, which is rather nucleophilic. A Hammett plot analysis of the addition reactions of the two radicals to substituted styrenes clearly support the nucleophilicity of benzoyl, but in the case of acetonyl, no satisfactory linear correlation with a single substituent‐related parameter was found. Computational calculations helped to rationalize this effect, and a good linear correlation was found with a combination of polar parameters ( σ + ) and the radical stabilization energies of the formed intermediates. Based on the calculated philicity indices for benzoyl and acetonyl, a quantitative comparison of these two radicals with many other reported radicals is possible, which may help to predict the reactivities of other aromatic radical substitution reactions. Abstract : Attraction and stability : The addition reactions of acetonyl and benzoyl radicals to substituted styrenes have been compared in an experimental and computational study. The results show that acetonyl is more electrophilic than benzoyl, which is rather nucleophilic. The relative rates of addition of acetonyl could only be rationalized by a combination of polar parameters ( σ + ) and the radical stabilization energies of the formed intermediates. The philicities of the radicals also affect the outcomes of aromatic substitution reactions.